Applying the Merdeka Curriculum: Development of Aqidah Akhlak Learning at State Madrasah Aliyah - Febriansyah, Riza; Achadi, Muh. Wasith (Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to determine the process of implementing the independent learning curriculum regarding moral beliefs in MAN 2 Sleman. This research is important to describe the independent curriculum in the learning process. The independent curriculum introduced by the Ministry of Education and Culture of the Republic of Indonesia aims to give students the freedom to develop their potential and interests. In the context of the Akidah Akhlak lesson, this curriculum directs teachers to focus on developing religious character and values in a contextual, project-based manner that focuses on real experiences. The research method used is qualitative with a case study approach. Data was obtained through observation and interviews at MAN 2 Sleman, which implemented the Merdeka Curriculum in the subject of moral faith. The results of the study show that implementing the Independent Curriculum in the subject of Moral Beliefs can increase active involvement in students, deepen their understanding of noble moral values, and encourage teachers to be more creative in designing learning materials relevant to daily life.